Obraz katolików i muzułmanów w polskich przekładach opowiadania Ivo Andricia U musafirhani - Małczak, Leszek (Przekłady Literatur Słowiańskich, 2011)
The picture of Bosnian Catholics and Muslims in the Polish translations of Andrić’s short story U musafirhani There are two Polish translations of Andrić’s short story U musafirhani. First one by Maria Znatowicz-Szczepańska was published in 1937. Second one by Alija Dukanović, Bosnian who settled and lived in Poland, was published in 1966. The story presents two Bosnians communities: Catholics and Muslims. The analysis of these two translations shows that the Catholic community is stonger in the Polish translations than in the original text. This tendency is more clear in Znatowicz-Szczepańska’s work. On the one hand the position of Catholics is much better and on the other hand their dependence on Muslims is smaller, as it was in real and as it is shown in Andrić’s pieace. In Dukanović’s translation there is a tendency to present Muslims in a better way as well. They are not so primitive, demanding and ruthless. Differences between translations corresponde with the context they were written. In the period between two world wars there was an antiphaty for the Muslim part of Bosnia which was treated as a dangerous element, warlike and communistlike. After The Second World War, during Communist times, rules unitarist ideology and it wasn’t coreect to emphasis civilizations, religious and national differences. It helps to understand both strategies of translations, why Marija Znatowicz-Szczepańska is very familiar with Catholics and very distanced from Muslims and at the same time why Alija Dukanović presents Muslims in a better way. Znatowicz-Szczepańska’s way of translation we can treat as domestication, Dukanović’s one as foreignization with strong element of the manipulation.